Enhancing Creative Thinking in High School Physics through Project-Based Learning Integrating Local Wisdom and STEAM for Quality Education - Meydiana Arnyan Putri; Khoirun Nisa' (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: The main goal of this study is to examine the impact of applying a Project-Based Learning (PjBL) model, grounded in local wisdom and integrated with a STEAM approach, on improving students' creative thinking skills in high school physics education. This objective aligns with the Sustainable Development Goals (SDGs), especially those focused on quality education. Method: This research employs a literature review methodology utilizing qualitative descriptive methods. It analyzes various national and international journals related to project-based learning based on local wisdom, published within the last five years. Results: In the research, work and project-based learning becomes discovery significantly enhances students' understanding of physics concepts. The study demonstrates that PjBL fosters deeper learning, allowing students to develop not only their comprehension of physics but also essential skills such as problem-solving, creativity, and teamwork in real-world contexts. Moreover, integrating local wisdom within the PjBL framework increases students' interest in cultural preservation and enhances their scientific literacy through hands-on project activities. Novelty: The novelty of the research lies in the unique integration of local wisdom into the PjBL STEAM framework, an area that remains relatively underexplored in existing literature. By combining these elements, the study contributes to innovative teaching methodologies aimed at improving academic outcomes while promoting cultural awareness and appreciation among students. This approach offers a fresh perspective on aligning educational practices with global educational goals, all while fostering the creativity and critical thinking skills essential for the 21st century.